Personality and expatriate performance: the mediating role of expatriate adjustment - Raduan Che Rose; Subramaniam Sri Ramalu; Jegak Uli; Naresh Kumar (2010)
This paper investigates the relationship between personality and job performance, and the mediating role of cross-cultural adjustment (CCA) in that relationship. Based on sample of 332 expatriates working in Malaysia, personality predicts job performance, and both the interaction and work adjustment mediates the relationship. The findings of this study contributes to the body of knowledge in the cross-cultural management field as well as practical implication to expatriating firms especially in the area of selection of international candidates